Son of Amity - Malae, Peter Nathaniel (Book collections on Project MUSE., 2018)
"Samoan-American author Peter Malae looks at Oregon lives that are often neglected in creative works about the Pacific Northwest region--veterans, immigrants, the incarcerated, the rural poor. This novel explores racism; the economic divide; Post-Traumatic Stress Disorder and the high cost of over-enlistment; recidivism of parolees; drug addiction; and sexual violence"--